2016
DOI: 10.1097/cin.0000000000000238
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Electronic Health Record Communication Skills

Abstract: This pilot study investigated nurse practitioner students' communication skills when utilizing the electronic health record during history taking. The nurse practitioner students (n = 16) were videotaped utilizing the electronic health record while taking health histories with standardized patients. The students were videotaped during two separate sessions during one semester. Two observers recorded the time spent (1) typing and talking, (2) typing only, and (3) looking at the computer without talking. Total h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…These studies found that the use of EHR had a positive effect on the physicians' tasks in an intensive care unit by allowing more time to be spent on clinical review with multiple physicians simultaneously and less time performing documentation and administrative work [31]. As indicated in a previous study, the use of EHR also enhances nursing communication skills when interacting and recording patient medical records [54].…”
Section: Discussionmentioning
confidence: 84%
“…These studies found that the use of EHR had a positive effect on the physicians' tasks in an intensive care unit by allowing more time to be spent on clinical review with multiple physicians simultaneously and less time performing documentation and administrative work [31]. As indicated in a previous study, the use of EHR also enhances nursing communication skills when interacting and recording patient medical records [54].…”
Section: Discussionmentioning
confidence: 84%
“…These studies found that the use of EHR had positive effect on the tasks of the physicians in an intensive care unit by allowing more time to be spent on clinical review with multiple physicians simultaneously and less time on performing documentation and administrative works [35]. As indicated in a previous study, the use of EHR also enhances nursing communication skills when interacting and recording patients' medical records [55].…”
Section: Discussionmentioning
confidence: 83%
“…These studies found that the use of EHR had a positive effect on the tasks of the physicians in an intensive care unit by allowing more time to be spent on clinical review with multiple physicians simultaneously and less time performing documentation and administrative work [35]. As indicated in a previous study, the use of EHR also enhances nursing communication skills when interacting and recording patient medical records [61].…”
Section: Discussionmentioning
confidence: 84%